Biocatalysis in the Recycling Landscape for Synthetic Polymers and Plastics towards Circular Textiles. Issue 19 (12th February 2021) - Jönsson, Christina; Wei, Ren; Biundo, Antonino; Landberg, Johan; Schwarz Bour, Lisa; Pezzotti, Fabio; Toca, Andreea; M. Jacques, Les; Bornscheuer, Uwe T.; Syrén, Per‐Olof
Abstract: Although recovery of fibers from used textiles with retained material quality is desired, separation of individual components from polymer blends used in today's complex textile materials is currently not available at viable scale. Biotechnology could provide a solution to this pressing problem by enabling selective depolymerization of recyclable fibers of natural and synthetic origin, to isolate constituents or even recover monomers. We compiled experimental data for biocatalytic polymer degradation with a focus on synthetic polymers with hydrolysable links and calculated conversion rates to explore this path The analysis emphasizes that we urgently need major research efforts: beyond cellulose‐based fibers, biotechnological‐assisted depolymerization of plastics so far only works for polyethylene terephthalate, with degradation of a few other relevant synthetic polymer chains being reported. In contrast, by analyzing market data and emerging trends for synthetic fibers in the textile industry, in combination with numbers from used garment collection and sorting plants, it was shown that the use of difficult‐to‐recycle blended materials is rapidly growing. If the lack of recycling technology and production trend for fiber blends remains, a volume of more than 3400 Mt of waste will have been accumulated by 2030. This work highlights the urgent need to transform the textile industry from a biocatalytic perspective. Abstract : Circular textiles : This Review highlights the urgent need to transform the textile industry from a biocatalytic perspective to enable fiber to fiber recycling of today's complex textile materials (renewable building blocks schematically represented by molecules sketched). If the production trend for synthetic textile fiber blends remains, a volume of more than 3400 Mt of waste will have been accumulated by 2030.